Clinical Profile of Post-Operative Treatment Duration in Pediatric Congenital Heart Disease Patients - Reido Dafa Annafis; I Ketut Alit Utamayasa; Heroe Soebroto (Universitas Malahayati Lampung, 2022)
ABSTRACT CHD (Congenital Heart Disease) is still a dangerous disease that causes a high infant mortality rate in the world. Nowadays, there are two groups of actions to treat congenital heart disease, surgical management and non-surgical management. This study discusses Clinical Profile of Post-Operative Treatment Duration in Pediatric Congenital Heart Disease Patients. Fourty medical records used for this analytical descriptive study were obtained from Department of Pediatrics and Department of Thoracic, Cardiac, and Vascular Surgeons, Dr. Soetomo General Hospital, Surabaya, Indonesia. This study described post operative treatment duration in pediatric congenital heart disease patients. The total patients in the study were 40 pediatric patients with the majority being female, namely 52.50% with higher mortality rate in patients with congenital heart disease with surgical treatment (16.6%). Most patients with CHD in children with surgical and non-surgical treatment were diagnosed in the infant age group (0-5 years), namely 31 patients (77.50%) with 5 surgical treatment patients and 26 non-surgical treatment patients. The majority of patients with congenital heart disease with surgical and non-surgical management in good nutritional status (60.00%). Most cases of cyanotic congenital heart disease are tetralogy of fallot (50%) with all of cases treated with cardiac catheterization for non-surgical treatment, zero case surgical treatment, and 5 cases without surgical or non surgical treatment. Acyanotic cases are ASD (28.56) with 4 cases cardiac catheterization, 2 cases treated with ASO device, and 1 case with ASD closure as surgical treatment. The duration of hospitalization after the procedure was shorter in good nutritional status (3.2 days) in both surgical and non-surgical treatment while shorter duration after procedure also appeared in cases of congenital heart disease with non-surgical treatment (4.25 days). CHD patients with non-surgical treatments have shorter duration compared to patients with surgical treatment. Most CHD cases were TOF for cyanotic and ASD for acyanotic with higher mortality rate in surgical treatment. Good nutritional status were found in both of the CHD treatment. Most CHD patients with surgical and non-surgical treatment were infant, female. Keywords: CHD, Surgical, Non-Surgical, Pediatrics, Treatment Duration